Phosphorus chemical shifts in a nucleic acid backbone from combined molecular dynamics and density functional calculations - Přecechtělová, Jana; Novák, Petr; Munzarová, Markéta L; Kaupp, Martin; Sklenář, Vladimír (Journal of the American Chemical Society, 2010)
A comprehensive quantum chemical analysis of the influence of backbone torsion angles on (31)P chemical shifts in DNAs has been carried out. An extensive DFT study employed snapshots obtained from the molecular dynamics simulation of [d(CGCGAATTCGCG)]2 to construct geometries of a hydrated dimethyl phosphate, which was used as a model for the phosphodiester linkage. Our calculations provided differences of 2.1 ± 0.3 and 1.6 ± 0.3 ppm between the B(I) and B(II) chemical shifts in two B-DNA residues of interest, which is in a very good agreement with the difference of 1.6 ppm inferred from experimental data. A more negative (31)P chemical shift for a residue in pure BI conformation compared to residues in mixed B(I)/B(II) conformation states is provided by DFT, in agreement with the NMR experiment. Statistical analysis of the MD/DFT data revealed a large dispersion of chemical shifts in both B(I) and B(II) regions of DNA structures. δP ranges within 3.5 ± 0.8 ppm in the B(I) region and within 4.5 ± 1.5 ppm in the B(II) region. While the (31)P chemical shift becomes more negative with increasing α in B(I)-DNA, it has the opposite trend in B(II)-DNA when both α and ζ increase simultaneously. The (31)P chemical shift is dominated by the torsion angles α and ζ, while an implicit treatment of β and ε is sufficient. The presence of an explicit solvent leads to a damping and a 2-3 ppm upfield shift of the torsion angle dependences.
Keywords: DNA, B-Form; molekulární konformace; rotace; sekvence nukleotidů; Molecular Dynamics Simulation; Base Sequence; Molecular Conformation; magnetická rezonanční spektroskopie; simulace molekulární dynamiky; kvantová teorie; B-DNA; Magnetic Resonance Spectroscopy; Quantum Theory; Rotation; fosfor; Phosphorus